Determining the Errors in Output Kinematic Parameters of Planar Mechanisms with a Complex Structure - W. Trzaska (International Journal of Applied Mechanics and Engineering, 2014)
The study is focused on determining the errors in output kinematic parameters (position, velocity, acceleration, jerk) of entire links or their selected points in complex planar mechanisms. The number of DOFs of the kinematic system is assumed to be equal to the number of drives and the rigid links are assumed to be connected by ideal, clearance-free geometric constraints. Input data include basic parameters of the mechanism with the involved errors as well as kinematic parameters of driving links and the involved errors. Output errors in kinematic parameters are determined basing on the linear theory of errors.